Analisis Perbandingan Efektivitas Strategi Pemasaran Konten (Content Marketing) antara Platform Instagram dan Tiktok dalam Meningkatkan Citra Merek Produk Dimsum Mentai Bitybite Pematang Siantar - Kristianto Kristianto; M Guntur Alamsyah Hasibuan; Diva Aulia; Rafika Dwi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This research explores how content marketing on Instagram and TikTok differs in its ability to shape the brand image of Dimsum Mentai BityBite in Pematang Siantar. Although both platforms are commonly utilized by culinary MSMEs, studies that directly compare their influence on brand perception are still scarce. To fill this gap, the study evaluates the performance of identical content uploaded on both platforms and examines how each medium contributes to audience engagement and the formation of brand impressions. Adopting a qualitative case study design, data were obtained through direct observation of two matched posts on Instagram and TikTok, supported by in-depth interviews with the business owner. Indicators of engagement such as the number of views, likes, comments, and shares were analyzed to understand user responses and the visibility generated by each platform. The findings indicate that TikTok delivers a wider reach and stronger interaction, largely due to its recommendation-driven algorithm and the appeal of concise, fast-paced videos. These features help accelerate public awareness and reinforce the image of a contemporary, trend-oriented brand. In contrast, Instagram offers greater advantages for maintaining consistent visual identity, fostering communication, and building long-term consumer trust. Its features allow the brand to sustain relational closeness and a stable identity. Overall, the study highlights that both platforms possess unique yet complementary strengths: TikTok is more effective for broad exposure and initial engagement, while Instagram supports loyalty and lasting brand attachment. Therefore, combining the advantages of both platforms can create a more effective and balanced strategy for brand development.